Detection of Shiga toxin-producing Escherichia coli (STEC) O157:H7, O26, O45, O103, O111, O121, and O145, and Salmonella in retail raw ground beef using the DuPont™ BAX® system - Wasilenko, Jamie L.; Fratamico, Pina M.; Sommers, Christopher; DeMarco, Daniel R.; Varkey, Stephen; Rhoden, Kyle; Tice, George (Frontiers in Cellular and Infection Microbiology, 2014)
Shiga toxin-producing Escherichia coli (STEC) and Salmonella are food-borne pathogens commonly associated with beef, and reliable methods are needed to determine their prevalence in beef and to ensure food safety. Retail ground beef was tested for the presence of E. coli O157:H7, STEC serogroups O26, O45, O103, O111, O121, and O145, and Salmonella using the DuPont™ BAX® system method. Ground beef (325 g) samples were enriched in 1.5 L of TSB with 2 mg/L novobiocin at 42°C for 18 h, and then evaluated using the BAX® System real-time PCR assays for E. coli O157:H7 and STEC suite, and the BAX® System standard PCR assays for E. coli O157:H7 MP and Salmonella. Samples positive for STEC target genes by the BAX® System assays were subjected to immunomagnetic separation (IMS) and plating onto modified Rainbow Agar O157. Enrichments that were PCR positive for Salmonella were inoculated into RV broth, incubated for 18 h at 42°C, and then plated onto XLT-4 agar. Presumptive positive STEC and Salmonella colonies were confirmed using the BAX® System assays. Results of the BAX® System STEC assays showed 20/308 (6.5%) of samples positive for both the Shiga toxin (stx) and intimin (eae) genes; 4 (1.3%) for stx, eae, and O26; 1 (0.3%) for stx, eae, and O45; 3 (1%) for stx, eae, and O103; and 1 (0.3%) for stx, eae, and O145. There were also 3 samples positive for stx, eae, and more than one STEC serogroup. Three (1.0%) of the samples were positive using the BAX® System real-time E. coli O157:H7 assay, and 28 (9.1%) were positive using the BAX® System Salmonella assay. STEC O103 and E. coli O157:H7 were isolated from 2/6 and 2/3 PCR positive samples, respectively. Salmonella isolates were recovered and confirmed from 27 of the 28 Salmonella PCR positive samples, and a portion of the isolates were serotyped and antibiotic resistance profiles determined. Results demonstrate that the BAX® System assays are effective for detecting STEC and Salmonella in beef.